Letter matching in word familiarity: comparing slot specific, relative position, and overlap coding approaches - Huebert, Andrew M., author; Cleary, Anne M., advisor; Seger, Carol A., committee member; Graham, Daniel, committee member; Marques, Luciana, committee member (Colorado State University. Libraries, 2023)
Familiarity detection is the sense that something has been encountered before, without being able to recall specifics of the encounter. Viewed as a separable process from recalling specifics, a growing body of research suggests that familiarity detection is an important cognitive process for a variety of reasons. Familiarity detection is thought to be driven by an overlap in features between stimuli stored in memory and a current stimulus. Research on familiarity detection suggests that letters are one significant contributing feature to word familiarity. An unexamined question is the extent to which letter overlap needs to occur in the same positions between existing memory representations and the current stimulus. Research on reading suggests that letters do not need to be in the exact correct location for lexical access to occur, with different theories specifying different constraints. One theory is that letter position is coded in terms of relativity; another is that letter position is coded in terms of general location with flexibility. For this dissertation, I conducted two experiments investigating how letter position processing might operate in word recognition without identification, which is thought to be a metric of familiarity detection. The results were consistent with letters being matched in terms of general location. Letters that were out of position that also did not maintain relativity still contributed to word recognition without identification to the same extent as letters in position. Implications for the mechanism behind feature matching are discussed.
Keywords: letter position; word familiarity; recognition memory; feature matching